Tax Minimization sebagai Pemoderasi Hubungan antara Tunneling Incentive, Bonus Mechanism dan Debt Convenant dengan Keputusan Transfer Pricing - Nuradila, Ratna Felix; Wibowo, Raden Arief (IAIN Surakarta, 2018)
This research is purposed to determine the effect of tunneling incentive, bonus mechanism and debt covenant to transfer pricing wich is moderated by tax minimization on multinational firm’s listed at Indonesian Stock Exchange in 2012-2014. The technique of this analysis is multiple regression analysis, wich used 33 annual report from secondary data with purposive sampling method. The result of this research showed that variabel which are having a significant impact to transfer pricing are tunneling incentive, debt covenant and moderation of tax minimization to tunneling incentive. Keywords: Transfer Pricing, Tunneling Incentive, Bonus Mechanism, Debt Covenant, Tax Minimization JEL Classification: H25, H71, M1